Yummy discourse a feminist discourse analysis of advertisements in selected Yummy Magazine issues - Garcia, Krisel D. (College of Arts and Letters, University of the Philippines Diliman, 2011)
This study examines the advertisements that contain images of women in Yummy Magazine issues January 2010 and January-February 2011. This study focuses on the projected identity of women, the significance of food to the Philippine society, and the relationship of the different signs in the ads. This study is conducted with the rationale that advertising is influenced by and also influences the concepts shared by the society. The analysis is done by examining the text and context within the framework of Guy Cook's model of an advertisement. Concepts from semiotics and discourse analysis underpin the approach in this study. Moreover, a feminist approach on discourse analysis is employed with regard to concepts of feminity. The analysis leads to the conclusion that the projected identities of women in the ads are associated with their stereotypical roles. Moreover, the analysis suggests that the significance of food lies in its involvement in the sphere of the family. With regard to the signs in the ads, the analysis shows that they interact with each other to create a unified concept.